Pedagogical Conditions for Improving Research Activity in Future Primary School Teachers - kizi , Khalilova Marjona Sobirjon; Mohirovna, Toyirova Nazokat (International Journal of Human Computing Studies, 2022)
The proverbs combine the life experiences of ancestors, their attitude to society, history, mood, ethical and aesthetic feelings, positive qualities. Examples of Turkic proverbs are first mentioned in Mahmud Kashgari's Devonu lug'otit turk. The article discusses the ways in which Uzbek folk proverbs are used in different situations.